Growth, nutrition, and soil respiration of a mycorrhiza-defective tomato mutant and its mycorrhizal wild-type progenitor - Cavagnaro, Timothy R; Langley, Adam J; Jackson, Louise E; Smukler, Sean M; Koch, George W (Functional plant biology : FPB, 2008)
The effects of colonisation of roots by arbuscular mycorrhizal fungi (AMF) on soil respiration, plant growth, nutrition, and soil microbial communities were assessed using a mycorrhiza-defective tomato (Solanum lycopersicum L.) mutant and its mycorrhizal wild-type progenitor. Plants were grown in rhizocosms in an automated respiration monitoring system over the course of the experiment (79 days). Soil respiration was similar in the two tomato genotypes, and between P treatments with plants. Mycorrhizal colonisation increased P and Zn content and decreased root biomass, but did not affect aboveground plant biomass. Soil microbial biomass C and soil microbial communities based on phospholipid fatty acid (PLFA) analysis were similar across all treatments, suggesting that the two genotypes differed little in their effect on soil activity. Although approximately similar amounts of C may have been expended belowground in both genotypes, they may have differed in the relative C allocation to root construction v. respiration. Further, net soil respiration did not differ between the two tomato genotypes, but root dry weight was lower in mycorrhizal roots, and respiration of mycorrhizal roots per unit dry weight was higher than nonmycorrhizal roots. This indicates that the AM contribution to soil respiration may indeed be significant, and nutrient uptake per unit C expenditure belowground in this experiment appeared to be higher in mycorrhizal plants.